Personal Strengths and Health Related Quality of Life in Dementia Caregivers from Latin America - Stephen K. Trapp; Paul B. Perrin; Richa Aggarwal; Silvina Victoria Peralta; Miriam E. Stolfi; Eliana Morelli; Leticia Aracely Peña Obeso; Juan Carlos Arango-Lasprilla (Behavioural Neurology)
The research literature has begun to demonstrate associations between personal strengths and enhanced psychosocial functioning of dementia caregivers, but these relationships have not been examined in the context of dementia caregivers in Latin America. The present study examined whether personal strengths, including resilience, optimism, and sense of coherence, were associated with mental and physical health related quality of life (HRQOL) in 130 dementia caregivers in Mexico and Argentina. Structural equation modeling found that the personal strengths collectively accounted for 58.4% of the variance in caregiver mental HRQOL, and resilience, sense of coherence, and optimism each had unique effects. In comparison, the personal strengths together accounted for 8.9% of the variance in caregiver physical HRQOL, and only sense of coherence yielded a unique effect. These results underscore the need to construct and disseminate empirically supported interventions based in part on important personal strengths, particularly sense of coherence, for this underrepresented group.